Creative Cultural Anthropology as a Methodology Principle - S. Z. Gontcharov (Russian State Vocational Pedagogical University, 2015)
The paper looks at the essence and prospects of creative cultural anthropology in the context of education, economy, labor and social wealth. The anthropology in question can become the methodology principle for a new historical social model arrangement as it originates from the universal abilities of the human race, developed on the moral basis of joint existence; productive creative force of man's integral subjectivity; and technological power reasonably combining the goals, means of production and creative forces of nature. The author outlines the prospective development ways for cultural anthropology guiding the educational system - the anthropological society basis - with the aim of developing a cultured, moral, socially and professionally competent personality; enforcing individual creative potentials; guaranteeing high status of teachers; and providing social communication forms giving place to self-activity of individuals and groups, and intellectual and cultural work. The author confirms the need for higher education available for everyone; otherwise, education, limited by the empirical level and primary vocational training, results in the rising portion of common labor in the national economy. The consequences lead to growing intellectual heterogeneity in the structure of aggregate activity; functional discord between the common and complex levels of labor; suspension of innovative technology implementation in production and management; aggravation of socio-cultural differences to the level of hostile opposition; abating competitiveness of Russia. The author makes the conclusion that, for the beneficial scenario of society development, the main emphasize should be on the socio-cultural expanded reproduction of man; the educational sphere should receive the A- group status, leaving the B-group status to material production.